Study of different type of the management of patients in cases of traumatic colorectal injury in tertiary hospital in West Bengal - Chandranath Banerjee,; Sajal Kumar Sarkar,; Shyamal Hansda,; Patra, Kajal Kumar (Asian Journal of Medical Sciences, 2022)
Background: Although the treatment strategy for colorectal trauma has advanced during the last part of the 20th century and the result has improved and compared to other injuries and problems, such as high septic complication rates and mortality rates, still exist, so standard management for colorectal trauma is still a controversial issue. Aims and Objectives: This study aims to determine the factors that affect morbidity and mortality in colon and rectum injuries. Materials and Methods: This study was prospective cohort study. The study was conducted at Burdwan Medical College and Hospital, West Bengal from May 2019 to October 2020 including 80 patient of trauma over abdomen. Thorough history taking and clinical examination were done. Template was generated in MS Excel sheet and analysis was done on statistical package for the social sciences software. Results: Among 80 patients, the majority of the patients were in the age group of 21–30 years (45%). Majority 69 patients (86.25%) were males and 11 patients (13.75%) were females. Gunshot wounds were found in maximum 41 (51.3%) and stab wounds in 27 (33.7%). Colon was injured in 68 (85%) patients and the rectum in 12 (15%) patients. CIS Grade 1, 2, and 3 was observed in 69 (86.3%) patients. Primary repair was performed in 45.0% (36) patients. Resection and anastomosis management was given to 32 (40.0%) patients. Conclusions: If colorectal injuries are not treated appropriately, severe complications leading to death may be induced; nonetheless, controversy still exists concerning the standard treatment. In this regard, unnecessary proximal diversions should be avoided.